2021
DOI: 10.3389/fmicb.2021.620309
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Thinning Influences the Rhizosphere Fungal Community Assembly of Pinus massoniana by Altering the Understory Vegetation Diversity

Abstract: Thinning can significantly promote forest productivity and ecological function. Rhizosphere fungi play an indispensable role in regulating nutrient cycling between plants and the environment, and their community composition can positively respond to anthropogenic disturbance. However, the initial effects of thinning on rhizosphere fungal community assembly have seldom been reported. In this research, we studied the alterations in the rhizosphere fungal communities of 29-year-old Pinus massoniana in East Sichua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The air-dried and sieved (<2 mm) soil samples were used to determine the soil's physicochemical properties, including pH, available phosphorus (AP), and alkaline nitrogen (AN). Soil pH was measured using a pH meter in a soil/water suspension (1:2.5 w/v) after shaking for 30 min [23,24]. The AN was determined using alkali diffusion methods.…”
Section: Determination Of Bioactive Ingredients Soil Physicochemical ...mentioning
confidence: 99%
“…The air-dried and sieved (<2 mm) soil samples were used to determine the soil's physicochemical properties, including pH, available phosphorus (AP), and alkaline nitrogen (AN). Soil pH was measured using a pH meter in a soil/water suspension (1:2.5 w/v) after shaking for 30 min [23,24]. The AN was determined using alkali diffusion methods.…”
Section: Determination Of Bioactive Ingredients Soil Physicochemical ...mentioning
confidence: 99%
“…Soil microorganisms play a crucial role in nutrient decomposition, absorption, and transformation in terrestrial ecosystems (Soong et al, 2019;Tian et al, 2019;Averill et al, 2021). The diversity and abundance of soil bacteria and fungi not only affect nutrient mineralization and cycling but are also sensitive to ecological environmental conditions, such as soil properties (Stark et al, 2012;Shen et al, 2013;Urbanová et al, 2015;Lladó et al, 2018), vegetation diversity (Liu et al, 2021;Shang et al, 2021), and climatic conditions (Bona et al, 2021). Soil properties are considered crucial factors influencing soil microbial activity and community structure, which have become a research hotspot in the field of the soil microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the asymmetric consumption of space, light, water, and soil nutrients by the overstory, understory vegetation often exists in a limited resource environment (Su et al, 2019). Previous studies have confirmed that light and soil conditions are generally considered to be the main limiting resources affecting the establishment and growth of understory vegetation (Nicotra et al, 1999;Stein et al, 2014;Zhou et al, 2016;Su et al, 2019;Liu et al, 2021). The reasons for these inconsistent results may be related to stand types, and for the mixed broadleaf-conifer forest, the response of vegetation diversity to light and soil environments was still unclear.…”
Section: Introductionmentioning
confidence: 99%